PERSEPSI RISIKO DAN KESIAPSIAGAAN TERHADAP BENCANA ASAP PADA MASYARAKAT KELURAHAN KAMPUNG DALAM KECAMATAN SIAK – RIAU - Sitti Chotidjah; Yolanda Frianka Sriputri; Anastasia Wulandari (Jurnal Manajemen Bencana (JMB), 2023)
Forest and land fires often occur in Riau Province which caused many negative impacts in everyday life. This study was to determine the relationship between risk perception and preparedness for smoke in Kampung Dalam, Siak – Riau. The sample were 504 respondent, age 20 – 39 years old, with 168 man and 336 woman. The risk perception instrument used the risk perception instrument from Dingde Xu, Yi Liu, Xin Deng, Chen Qing, Linmei Zhuang, Zhuolin Yong and Kai Huang (2019). The preparedness instrument was from LIPI and UNESCO. Both instruments were modified according to research problems. The data analysis technique used a simple regression analysis technique. The results showed a significance value of 0.000 (< 0.05) with R Square 0.039. It means there was relationship between risk perception and preparedness for smoke with 3.9% contribution from risk perception. T-test for risk perception showed that occupation had significant contribution, housewife had highest risk perception for smoke. However there was no differences significant in preparedness for smoke.